Increased lowland rice production in the Mekong region (Australian Centre for International Agricultural Research, 1982)
The main objective of the workshop was to exchange available information that would assist development of rice-based cropping systems in Southeast Asia, particularly in laos and Cambodia. The workshop focused on the following areas. understanding the impact of environmental constraints and method to minimize the constraints, particularly for drought and low soil fertility in rainfed lowland rice and low temperature in dry season irrigated rice. development of rice breeding strategies for stress environments, and characterization of environment factors that are constraints for rice production in the region and mapping weather and soil related factors using crop modelling and GIS.